2019
DOI: 10.31501/esf.v0i14.10387
|View full text |Cite
|
Sign up to set email alerts
|

Midiativismo em rede: Twitter e as críticas aos meios de comunicação tradicionais em um sistema híbrido de comunicação

Abstract: Este artigo propõe uma discussão sobre a relação entre o uso do Twitter durante as manifestações de 2013 no Brasil e a reconfiguração do sistema de comunicação. Partimos dos conceitos de sistema híbrido de comunicação e de midiativismo para entender o uso das mídias sociais como parte de um ambiente comunicacional mais amplo e que se modifica com a presença destas novas mídias. Em seguida analisamos um corpus de 6.256 tweets que citam os meios de comunicação tradicionais para compreender a forma esses meios sã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In the Brazilian reality historically, criticism of the media has been built as part of the Brazilian left-wing agenda, emerging with the struggle for press freedom during the military dictatorship until the movements against media concentration after democratization (strongly active after the re-democratization process, from the nineties on). By 2013, this phenomenon had already spread throughout society, causing the media, especially Rede Globo, to be accused of trying to overthrow President Dilma Rousseff and, at the same time, working for her re-election (Santos, Almada, 2019). Such processes seem to have accentuated even further over recent years, increasing criticism of the traditional media on the part of the rightwing 10 , which may be due to the fact that a right-wing political party has reached presidency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian reality historically, criticism of the media has been built as part of the Brazilian left-wing agenda, emerging with the struggle for press freedom during the military dictatorship until the movements against media concentration after democratization (strongly active after the re-democratization process, from the nineties on). By 2013, this phenomenon had already spread throughout society, causing the media, especially Rede Globo, to be accused of trying to overthrow President Dilma Rousseff and, at the same time, working for her re-election (Santos, Almada, 2019). Such processes seem to have accentuated even further over recent years, increasing criticism of the traditional media on the part of the rightwing 10 , which may be due to the fact that a right-wing political party has reached presidency.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not simply a matter of receiving information from certain sources, but of receiving it through certain social bonds (that often feed into digital media). Previous research has shown how instant messaging applications are pivotal spaces for the circulation of such messages (Santos et al, 2019), suggesting the need for further research across different platforms and communication spaces. The paper has shown the need for understanding mediation in terms of both its complexification by various digital communicative spaces and its diverse appropriations by different social groups in their attempts to formulate their discourses.…”
Section: Discussionmentioning
confidence: 99%
“…Na esteira de Harlow (2011, p. 228), entendemos aqui o ativismo como ações coletivas com fins de mudança social, sejam advindas de movimentos sociais mais clássicos ou de ações mais pontuais. O deba-te teórico sobre ativismo online (e suas variações terminológicas e práticas) (Bachini;Ceneviva, 2017;Melo, 2016) e o acompanhamento de pautas, grupos ou sujeitos ativistas nas redes digitais atravessam os textos apresentados nos eventos, mas se espraiam para além deles, configurando-se como faces centrais da área Santos, 2017a;Garcêz et al, 2020;Penteado, 2020;Almada, 2019). Como já diagnosticado por Sampaio et al (2018), quando observado apenas o GT Ciberpolítica da ANPOCS, o segundo objeto mais recorrente são movimentos sociais e organizações cívicas.…”
Section: Comunicação E Ativismosunclassified
“…Trata-se de uma pluralização notável não apenas nos temas, 303 mas também nas universidades de origem dos pesquisadores. Outro foco interessante é o chamado midiativismo, quando as redes sociais são utilizadas para se contrapor e criticar os meios de comunicação tradicionais a partir de novos mediadores Almada, 2019). Há também estudos sobre o ativismo de grupos religiosos na internet e sua influência sobre processos eleitorais (Barreras;Weber, 2015).…”
Section: Comunicação E Ativismosunclassified